PENGARUH IKLIM ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI UNIVERSITAS SERANG RAYA - Rahmi Mulyasih; Siska Mardiana (LONTAR: Jurnal Ilmu Komunikasi, 2015)
This research is conducted to know whether organization climite and work discipline have influence toward the increasing of employee performance at Serang Raya University, and also to know which one of the variable that has more influence on the performance of employees at that company. The hypothesis in this research is that the climite organization and work discipline have influence on the performance of Serang Raya University, with quantitative research methode.The population of the research obtained from the employees of Serang Raya Universitu with the sampling method used Slovin formula and resultsÂ  60respondents of sample. the research instrument use questionnaires with likert scale, for validity and reliability examined with SPSS 20 program. For data analysis the researcher uses multiple regression analysisPartially, tthe work discipline variables have more infuence than climite organization variables on the performance of employees at Serang Raya University.The result of the research denotes that variables of climite organizations and work discipline simultaneously have influence toward the increasing employee performance, the contribution is 27,50% while the remaining 72,50% influenced by other variables those are not included in this research. Â Key Words: Organizational Climate, Work Discipline, Performance.Â